Sharia, Two Sides of the Same Coin: The Contradictions between Sharia and Adat (Case Studies of Minangkabau’s Matrilineal and Land Tenure System) - Adri Wanto (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
Since the implementation of regional autonomy laws in Indonesia, large numbers of sharia-inspired laws have been implemented in the West Sumatera Province. Furthermore, some Minangkabau people, the ethnic group indigenous to the province, have insisted in the abolishment of the matrilineal and land tenure system, which they believe is not in accordance with sharia. For hundreds of years, the Minangkabau ethnic have been famous for being one of the world’s largest matrilineal societies, and the inheritance of land and property ownership is handed down according to the matrilineal principle over generations. As a result, conflicts arise within indigenous communities (internal conflict-horizontal) since its proponents and opponents are equally strong in the society. The most interesting aspect to be analyzed is the fact that the disputing groups use sharia to legitimize their points of view. Some argue that the matrilineal and land tenure system is in accordance with sharia while others argue otherwise. This study will focus on the discourse beyond the epistemic claim made by the disputing groups. This paper argues that the mix of ideological, political and economic interests play a significant role behind the struggle for control of the religious discourse, particularly related to the matrilineal and the land tenure system in the Minangkabau post reformasi era.